PENGARUH BANTUAN PRESIDEN BLT UMKM TERHADAP PRODUKTIVITAS USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN BATANG - Majid, Abdul; Kurniawan, Devi Dwi; Sigit, Kharisma Nawang (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
Research on the Effect of Presidential Aid BLT UMKM on Productivity of Micro, Small and Medium Enterprises in Batang Regency aims to find out how UMKM working capital assistance affects the productivity of UMKM actors and to find out how the influence of this UMKM working capital assistance program has an effect on increasing the economic growth of UMKM actors in the Regency. Trunk. The research method used is quantitative, where data is obtained by distributing questionnaires to recipients of the MSME working capital Banpres while for sampling using a random sampling technique where a sample of 233 Banpres MSME recipients is obtained. Data analysis uses a regression formula. The results showed that 1) MSME working capital assistance had an effect on the productivity of MSME actors, 2) MSME working capital assistance had an effect on increasing the economic growth of MSME actors in Batang Regency